2003
DOI: 10.1042/bj20021030
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal-growth-factor receptor and metalloproteinases mediate thromboxane A2-dependent extracellular-signal-regulated kinase activation

Abstract: The signalling pathways that link G-protein-coupled receptors to mitogen-activated protein kinases involve receptor and non-receptor tyrosine kinases and protein kinase C (PKC). We explored the pathways that are implicated in the thromboxane (TX) A(2)-dependent activation of extracellular-signal-regulated protein kinase (ERK) and the role of the two TX receptor (TP) isoforms, TP alpha and TP beta. ERK activation by IBOP, a TX analogue, was dependent on epidermal-growth-factor receptor (EGFR) in TP alpha- or TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…We have demonstrated that I-BOP induced rapid activation of ERK primarily through EGFR pathway since EGFR inhibitor blocked phosphorylation almost totally. TP-mediated transactivation of EGFR in eventual activation of ERK has also been reported in several cell lines [8][9][10]. In addition to EGFR, other signaling pathway such as activation of PKC was shown to involve in ERK activation in these cell lines although we did not see PKC being involved in a significant way in A549 cells.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…We have demonstrated that I-BOP induced rapid activation of ERK primarily through EGFR pathway since EGFR inhibitor blocked phosphorylation almost totally. TP-mediated transactivation of EGFR in eventual activation of ERK has also been reported in several cell lines [8][9][10]. In addition to EGFR, other signaling pathway such as activation of PKC was shown to involve in ERK activation in these cell lines although we did not see PKC being involved in a significant way in A549 cells.…”
Section: Discussionsupporting
confidence: 40%
“…ERK phosphorylation mediated by TP activation was extensively studied by several groups [8][9][10]. We have demonstrated that I-BOP induced rapid activation of ERK primarily through EGFR pathway since EGFR inhibitor blocked phosphorylation almost totally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of GPCR-mediated metalloprotease activation is not fully understood, and several signaling molecules have been implicated in this process in various cell types (6,8,25,26). We have recently shown that both Src and Pyk2 have important roles in GnRH-induced ERK1/2 activation in GT1-7 cells (11).…”
Section: Fig 3 Hb-egf Production Through Metalloprotease Activationmentioning
confidence: 99%
“…GPCRs transactivate EGFR via several mechanisms [20,21]. One mechanism involves the activation of a membrane-bound metalloproteinase that catalyzes the extracellular shedding of HB-EGF, which then actives the EGFR [22][23][24][25]. A second mechanism involves the activation of c-Src, which leads to the phosphorylation and activation of EGFR [26][27][28].…”
Section: Introductionmentioning
confidence: 99%